Pengaruh Metode Takrir Terhadap Penguatan Hafalan Al-Qur’an Surah Pendek Bagi Siswa Mis Mamba’ul ‘Ulum Sigambal Kabupaten Labuhanbatu - Patimah Pasaribu; Suryatik; Leli Hasanah Lubis; Dwina Putri (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study uses a quantitative approach with a saturated sampling technique, where all students in the class are included as samples. The experimental class consisting of 19 students was taught using the Takrir Method, while the control class consisting of 19 students was taught using the Sima'i Method. The instrument used in this study was an oral test with 16 questions designed to measure students' memorization abilities for short surahs. Data analysis was carried out using a paired t-test at a significance level of α = 0.05. The results of the hypothesis testing showed that the t-count value was greater than the t-table (4.546> 1.696). Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, which means that there is a significant effect of the use of the Takrir Method on strengthening the memorization of the Qur'an in grade IV students at MIS Mamba'ul Ulum Lingga Tiga. In conclusion, this study proves that the Takrir Method is effective in improving memorization of the Qur'an in short surahs, which can be used as a consideration in the Tahfizh teaching method in Islamic schools. This finding has important implications in the development of Islamic education curriculum, especially in the field of Tahfizh Al-Qur'an